Perilaku Diet Gizi Seimbang Di Kalangan Mahasiswa: Psychonutrition Teori Sistem Ekologi Dan Health Belief Model - nyono_dedi_prabowo, nyono_dedi_prabowo; Nurul Hidayah; Septia Purwandani; Rizky Aulia Fitriana; Mifta Wahyu Rafa Sakina (Guidance and counseling the university of Prof. Dr. Hazairin. SH, 2024)
Dietary trends have gained a lot of attention in the last ten years, particularly among young adults. A new reset point for dietary behavior modifications has been established by the Covid-19 pandemic. Indonesian dietary guidelines advocate a healthy, balanced diet based on the